Write a rule for the nth term of the sequence. Use your rule to find a70.

–10, –8, –6, –4, –2, . . .

To find the rule for the nth term of the sequence, we can observe that each term is obtained by adding 2 to the previous term. Therefore, we can express the nth term as:

an = an-1 + 2

Where a1 = -10 (the first term).

Now, to find a70, we can use the formula:

a70 = a69 + 2

To find a69, we can apply the formula again:

a69 = a68 + 2

And so on, until we reach a1.

Substituting the values into the equation, we have:

a69 = a68 + 2
a69 = -2 + 2
a69 = 0

a70 = a69 + 2
a70 = 0 + 2
a70 = 2

Therefore, the 70th term of the sequence is 2.

To find a rule for the nth term of the sequence -10, -8, -6, -4, -2, ..., we can observe that each term is obtained by adding 2 to the previous term. Therefore, the rule for the nth term can be expressed as:

an = -10 + 2(n - 1)

To find a70, we substitute n = 70 into the formula:

a70 = -10 + 2(70 - 1)
= -10 + 2(69)
= -10 + 138
= 128

Hence, a70 is equal to 128.

an = -10 + [2 * (n - 1)]